Mitigation And Adaptation Peatland Through Sustainable Agricultural Approaches In Indonesia: In A Review - Soni Sisbudi Harsono (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2020)
Rapid and massive damage on peatland mainly due to conversion to a production system in the presence of perennial crops for the purpose of financially profitable agribusiness, such as oil palm plantations and other industries, can lead to increased greenhouse gases. Greenhouse gas emissions are influenced by biophysical processes are complex, such as peat decomposition and compaction, nutrient availability, soil water content, and soil water content. When land clearing increased significantly in the area of peatland is not followed by the application of sustainable agriculture, then, will peat land would become flammable and the greater the volume of CO2 gas that emits into the atmosphere that causes global warming and climate change. This paper reviews about the expansion of agriculture and plantations on peatland and action needs to be done by following sustainable agricultural systems. Noting the condition of peatland that have been severely damaged due to the expansion of oil palm plantations, the mitigation and adaptation in the land through sustainable agricultural system is highly recommended to reduce the more severe damage to the peatland areas and minimize the release of CO2 into the atmosphere.